Enhanced electrocaloric effect of P(VDF-TrFE)-based nanocomposites with Ca and Sn co-doped BaTiO3 particles. Issue 2 (15th January 2023) - Tokkan, Melike; Demir, Mustafa M.; Adem, Umut
Abstract: We report on the enhancemenent of electrocaloric effect in solution cast polymer nanocomposites based on Poly(vinylidene fluoride- co -trifluoroethylene) [P(VDF-TrFE) 55-45] with Ca and Sn co-substituted BaTiO3 ceramic fillers (Ba0 .94 Ca0.06 Ti0.925 Sn0.075 O3, BCST). Saturated hysteresis loops and normal ferroelectric behaviour of the copolymer-based nanocomposites -as opposed to the relaxor ferroelectric nature of the terpolymer-based ones-allow the utilization of the indirect method to estimate the electrocaloric properties. Both the dielectric constant and electrocaloric temperature change (ΔT) increases as the particle content increases. Maximum adiabatic temperature change was obtained as 6.96 K under 900 kV/cm for the 10 vol % BCST containing polymer composite around the Curie temperature of the copolymer (70 °C). This relatively large electrocaloric strength is slightly lower than those obtained for terpolymer-based nanocomposites.